MexXY RND pump of Pseudomonas aeruginosa PA7 effluxes bi-anionic β-lactams carbenicillin and sulbenicillin when it partners with the outer membrane factor OprA but not with OprM. Issue 11 (10th December 2020) - Singh, Manu; Sykes, Ellen M. E.; Li, Yanqi; Kumar, Ayush
Abstract : Antibiotic resistance in Pseudomonas aeruginosa is a serious concern in healthcare systems. Among the determinants of antibiotic resistance in P. aeruginosa, efflux pumps belonging to the resistance–nodulation–division (RND) family confer resistance to a broad range of antibacterial compounds. The MexXY efflux system is widely overexpressed in P. aeruginosa isolates from cystic fibrosis (CF) patients. MexXY can form functional complexes with two different outer membrane factors (OMFs), OprA and OprM. In this study, using state-of-the-art genetic tools, the substrate specificities of MexXY–OprA and MexXY–OprM complexes were determined. Our results show, for the first time, that the substrate profile of the MexXY system from P. aeruginosa PA7 can vary depending on which OM factor (OprM or OprA) it complexes with. While both MexXY–OprA and MexXY–OprM complexes are capable of effluxing aminoglycosides, the bi-anionic β-lactam molecules carbenicillin and sulbenicillin were found to only be the substrate of MexXY–OprA. Our study therefore shows that by partnering with different OMF proteins MexY can expand its substrate profile.